The Study on Effects of Foreign Ownership on Innovation (Asian Business Research, 2016)
In developing countries, government actively promotes foreign investment in order to adapt the new and latest technology. This leads to greater R&D activities, thus this creates knowledge and technology spillover. In this paper, we look at Korea where the R&D has been the main factor of rapid growth. We study the effects of foreign ownership on technological performance by looking at 756 R&D intensive Korean firms from 1999 to 2009. We look the number of applied and registered patents are dependent variables (as a technological performance) and observe statistically significant and positive correlation with foreign ownership due to threemain reasons: (a) knowledge and technology spillover, (b) relatively more risk-taking investment behavior ofinstitutional investors, and (c) cherry-picking strategy of investing in firms that perform well. Furthermore, wealso observe the R&D expenditure has a strong and positive correlation with the number of applied andregistered patents, and R&D expenditure could serve as a proxy variable for technologically advanced industries.Lastly, we observe that the coefficients increase for applied and registered patents for different technology indexsub-groups